2009
DOI: 10.1055/s-0028-1128141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Intravenous Glucocorticoids and Orbital Radiotherapy in Restoring Driving Competency in Patients with Graves’ Orbitopathy

Abstract: Intravenous glucocorticoids and orbital radiotherapy are effective treatments for moderate-to-severe and active Graves' orbitopathy. We examined the ophthalmological outcome in daily life activities, such as driving competency. In a retrospective case series, 23 patients with moderate-to-severe and active Graves' disease (14 women and 7 men) were consecutively treated with combined orbital radiotherapy (13 Gy) and intravenous methylprednisolone (500 mg weekly for 6 consecutive weeks and 250 mg weekly for conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
2
1
1
Order By: Relevance
“…Although alterations in ocular motility were our primary concern, CAS as well as SIR was also assessed in all patients pretreatment and posttreatment and this may represent the first attempt in the literature to apply a modern assessment consensus in combined treatment regimens for TED. Overall improvement in CAS was found to be statistically significant and positively comparable to recent studies that involve pulse steroid treatment alone (17). Improvement in TED-related myopathy correlates to low CAS scores after treatment in this series of patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although alterations in ocular motility were our primary concern, CAS as well as SIR was also assessed in all patients pretreatment and posttreatment and this may represent the first attempt in the literature to apply a modern assessment consensus in combined treatment regimens for TED. Overall improvement in CAS was found to be statistically significant and positively comparable to recent studies that involve pulse steroid treatment alone (17). Improvement in TED-related myopathy correlates to low CAS scores after treatment in this series of patients.…”
Section: Discussionsupporting
confidence: 83%
“…Other therapeutic options such as orbital radiotherapy and second-line immunosuppressants (12, 13) such as azathioprine (AZA) and cyclosporine, nonsteroidal anti-inflammatory drugs, and, more recently, biological agents (14, 15) have been proposed with success rates that vary according to different studies. Combined regimens have often been tried aiming to achieve better efficacy while reducing steroid-related adverse effects (16, 17). We have routinely used combined treatment protocols for 10 consecutive years in patients with severe, active, noncompressive TED using the onset of motility restriction as indication for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This probably means that side differences often persist despite motility improvements. Our rate is lower in comparison to trials of and Sterker et al (2009), who reported disappearance of diplopia in primary position in more than half of the patients due to iv GCs alone [23,45]. In the study of Kahaly et al the patients were treated even earlier (mean duration of GO 3-4 months) than the patients in our study.…”
Section: Treatment Response Of Single Manifestationscontrasting
confidence: 72%
“…All 3 doses were effective; treatment with one Gy per week for 20 weeks was tolerated better [113]. A lower dose appears to be less effective in terms of improving ocular motility, but the soft tissue findings still improved [111,114]. Two large retrospective studies further investigated the extent to which radiotherapy influenced the development of compressive optic neuropathy.…”
Section: Orbital Apex Irradiationmentioning
confidence: 99%
“…Alle 3 Dosierungen waren wirksam, die Therapie mit 1 Gy pro Woche über 20 Wochen erwies sich als besser verträglich 113 . Eine niedrigere Dosierung scheint hinsichtlich der Motilitätsverbesserung weniger wirksam, es bessern sich aber immer noch die Weichteilbefunde 111 , 114 . In 2 großen retrospektiven Studien wurde weiterhin untersucht, inwieweit eine Strahlentherapie die Entwicklung einer kompressiven Optikusneuropathie beeinflusst.…”
Section: Alle Therapieansätze Im Detailunclassified